Urban microgrid ancillary service provision using plugin electric vehicle and waste-to-energy CHP. (June 2020) - Ghaebi Panah, Payam; Hooshmand, Rahmat-Allah; Gholipour, Mehdi; Bornapour, Mosayeb
Highlights: Aggregation of Plugin Electric Vehicle parking lots and Waste to Energy CHP in an Urban Micro Grid. Data analysis on driving behaviors and regulating power markets to extract the patterns and clusters. Simultaneous participation in District Heating, Day-ahead, and Regulating Up/Down markets. Crow Search Algorithm to maximize the "Market Value of Energy" as the objective function. Abstract: Today in developed megacities, municipal waste incinerators are a practical solution although they require a relatively high initial investment. On the other hand, E-Transport is growing in metropolitans along with the Renewable Energy Sources (RES). This study proposes an Urban Micro Grid (UMG) consisting of a Waste-to-Energy Combined Heat and Power generation unit (WtE-CHP) and series of Plugin Electric Vehicles (PEV). The main purpose is to provide ancillary services through the incorporation of PEVs as fast-responsive storages. The parking lots may aggregate to form PEV clusters and make bilateral contracts with WtE-CHP to be able to participate in the regulating power markets. A Crow Search Algorithm (CSA) is developed for the UMG operation. In addition, a data analysis section is provided focusing on the behavior of urban drives to extract the realistic probabilities for PEVs available during the daytime. Moreover, the power market of Denmark east (DK2) is considered for the case study of Copenhagen. The results confirm that in case the UMG succeeds in selling the products in the regulating up market, the economic value per MW is remarkably enhanced and the total profit is escalated.